Peran Sekolah Tahfidz dalam Pembentukan Generasi Qur'ani Berwawasan Sains: Studi Kasus di Pesantren Sekolah Menengah Sains Tahfidz Alor Setar Kedah, Malaysia - Mawardi; Lazuardi Muhammad Latif; Juwaini; Afkar Azizi; Muhammad Syafiq bin Asli; Ahmad Irfan Firdaus Bin Jamaluddin; Nelsa Erdarisna; Muhammad Aidil Rifky; Muhammad Alwi Syahputra; Arif Rahmani; Nandini; Cut Ade Kurnia Saifa Alhajd Quraisy; Zuhari Alvinda Haris; Rifky Al Kautsar; Aulia Raysa Yani (Jurnal Riset dan Pengabdian Masyarakat, 2025)
This journal aims to describe the role of Pesantren Sekolah Menengah Sains Tahfidz (Semesti) Alor Setar, Kedah, Malaysia in shaping a Qur’anic generation with a scientific outlook. This research is part of the Community Service Program (KPM) carried out by students of the Faculty of Ushuluddin and Philosophy, UIN Ar-Raniry Banda Aceh, at the institution. The main focus of the study is the integration of Qur’an memorization (tahfidz) with the strengthening of science subjects at the secondary school level. The KPM activities conducted, such as tasmi’ (Qur’an recitation), teacher assistance, exam supervision, and organizing competitions, became a medium for us to directly observe how a Qur’anic generation with scientific insight is formed. The method used in this study is a qualitative approach through field observation, interviews with the pesantren’s staff, and active participation in learning activities. The findings indicate that the implementation of the tahfidz program combined with the science curriculum is carried out systematically, both through regular learning schedules and extracurricular activities. Furthermore, the boarding school system also contributes to shaping students’ religious character and discipline. The integration of science subjects within the pesantren environment enables students not only to focus on memorization but also to gain applicable scientific understanding. This research is expected to serve as a reference for other educational institutions that wish to develop an integrative education model between tahfidz and science.